ANALISIS KUALITAS BUTIR SOAL ASESMEN SUMATIF AKHIR SEMESTER GENAP PELAJARAN MATEMATIKA MI - Wibowo, Eko Ari; Sabrina, Dalila; Laili, Risalah Nur; Sutarni, Sri; Hidayati, Yulia Maftuhah (Universitas Bhinneka PGRI, 2026)
Assessment of learning outcomes is an essential aspect in the learning process to measure students' competency achievement. This study aims to analyze the quality of summative assessment questions at the end of the even semester in Mathematics at Madrasah Ibtidaiyah (MI). The analysis was carried out on five main aspects: validity, reliability, level of difficulty, discriminatory power, and distractor effectiveness. The study used a descriptive quantitative approach with data obtained from question documents, answer keys, and answer sheets of grade V students (n = 26). Data analysis techniques included point biserial correlation for validity testing, Cronbach's Alpha for reliability, and classical formulas for level of difficulty, discriminatory power, and distractor effectiveness. The results showed that 64% of the questions were valid, the reliability of the questions was quite high (α = 0.78), 40% of the questions were categorized as moderate difficulty, and 60% had good to very good discriminatory power. However, there were 36% of questions that were invalid and some distractors did not function optimally. These findings indicate that the quality of the questions is generally quite good, but revisions need to be made to less than optimal question items to improve the effectiveness of the assessment.